Expression and characterization of the ferritin binding domain of Nuclear Receptor Coactivator-4 (NCOA4) - Gryzik, Magdalena; Srivastava, Ayush; Longhi, Giovanna; Bertuzzi, Michela; Gianoncelli, Alessandra; Carmona, Fernando; Poli, Maura; Arosio, Paolo (Biochimica et biophysica acta. General subjects, 2017)
Ferritinophagy is the process of autophagic degradation of ferritin that participates in the regulation of cellular iron homeostasis. This process was shown to be mediated by the selective cargo-receptor Nuclear Receptor Coactivator-4 (NCOA4) that binds ferritin and targets it to emerging autophagosome. To characterize some of the biochemical properties of the interaction between the two proteins we cloned and expressed in E. coli the ferritin-binding domain of human NCOA4, fragment 383–522. It was purified and subjected to biochemical analysis. The NCOA4(383–522) fragment was expressed in soluble and dimeric form, and CD spectra indicated low level of secondary structure. The Ferritin binding activity of the fragment was investigated by developing an electrophoretic mobility shift and an ELISA assays. They showed that the NCOA4 fragment binds the H-ferritin with an affinity in the nM range, but not the R23A H-ferritin mutant and the L-ferritin chain, confirming the high specificity for the H-chain. The H-ferritin could bind up to 24 NCOA4(383–522) fragments forming highly stable and insoluble complexes. The binding was partially inhibited only by Fe(II) among the various divalent metal ions analyzed. The iron-dependent, highly-specific formation of the remarkably stable H-ferritin-NCOA4 complex shown in this work may be important for the characterization of the mechanism of ferritinophagy. •The recombinant ferritin binding domain of NCOA4 (residues 383-522) was expressed in E. coli and purified.•The domain binds ferritin H-chain with high affinity, but not its mutant Arg23Ala and ferritin L-chain•Electro mobility shift assay showed that H-ferritin binds up to 24 NCOA4 domains forming a highly stable complex•ELISA assay showed that the complex formation is partially inhibited by Fe(II) but not by other divalent metal ions.